2002
DOI: 10.2139/ssrn.298879
|View full text |Cite
|
Sign up to set email alerts
|

An IV Model of Quantile Treatment Effects

Victor Chernozhukov,
Christian Hansen

Abstract: Headnote.The ability of quantile regression models to characterize the heterogeneous impact of variables on different points of an outcome distribution makes them appealing in many economic applications. However, in observational studies, the variables of interest (e.g. education, prices) are often endogenous, making conventional quantile regression inconsistent and hence inappropriate for recovering the causal effects of these variables on the quantiles of economic outcomes. In order to address this problem, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
585
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(598 citation statements)
references
References 38 publications
10
585
2
1
Order By: Relevance
“…Using these CPI data, we construct 1-year-ahead ex post core inflation 6 rates and, 3 Although Chevapatrakul et al (2009) present data up to 2005 for Japan, their estimation uses a sample that ends before February 1999, to study the monetary policy when the ZLB is approached. 4 The 2SQR methodology is based on the fitted value approach, which extends Amemiya (1982), whereas the IVQR method builds on the instrumental variable approach suggested by Chernozhukov and Hansen (2005, 2008. 5 The call rate data are available from July 1985 at the Bank of Japan's web site.…”
Section: Datamentioning
confidence: 99%
“…Using these CPI data, we construct 1-year-ahead ex post core inflation 6 rates and, 3 Although Chevapatrakul et al (2009) present data up to 2005 for Japan, their estimation uses a sample that ends before February 1999, to study the monetary policy when the ZLB is approached. 4 The 2SQR methodology is based on the fitted value approach, which extends Amemiya (1982), whereas the IVQR method builds on the instrumental variable approach suggested by Chernozhukov and Hansen (2005, 2008. 5 The call rate data are available from July 1985 at the Bank of Japan's web site.…”
Section: Datamentioning
confidence: 99%
“…As in the classical 2SLS, median uncorrelation leads to an estimator that is derived by taking a "sample analogue" of the median uncorrelation measure. This estimator, similar to one used by Chernozhukov and Hansen (2005) (or CH) , is consistent provided that this uncorrelation holds (along with other standard assumptions). Other applications are natural counterparts of existing least squares methods.…”
Section: Introductionmentioning
confidence: 57%
“…There are a set of papers that deal with endogeneity in linear (and nonlinear) quantile based models. See for example Amemiya (1981) for a 2 stage interpretation of the 2SLS, and Chernozhukov and Hansen (2005) for an approach to inference in quantile based models, both linear and nonlinear, in the presence of endogenous regressors.…”
Section: Median Uncorrelation and Instrumental Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benkard and Berry (2006) showed that this claim is incorrect, leaving uncertain the nonparametric identifiability of fully simultaneous models. Completeness conditions (Lehmann andScheffe (1950, 1955)) offer one possible approach, and in Berry and Haile (2014a) we showed how identification arguments in Newey and Powell (2003) or Chernozhukov and Hansen (2005) can be adapted to an example of the class of models considered below. 3 However, independent of general concerns one might have with the interpretability of completeness conditions, this approach may be particularly unsatisfactory in a simultaneous equations setting.…”
Section: Introductionmentioning
confidence: 97%